Kompetencja międzykulturowa w nauczaniu języka polskiego jako obcego - Urszula Żydek-Bednarczuk (Postscriptum Polonistyczne)
In the article the following terms have been revised: competences, communicative competence, intercultural competence. The classification of some new competences required in glottodidactics has been suggested. In the presented model the intercultural competence has been included and its relationship with other competences has been described. The guidelines of Common European Framework of Reference for Languages have been discussed here. Educational application has shown how the new competences should be developed.